Domestic Politics, Foreign Interests, and International Trade Policy: Reply - Hillman, Arye L.; Ursprung, Heinrich W. (American Economic Review, 2016)
This paper incorporates the foreign interest in the determination of a country's international trade policy into a model of political competition between candidates contesting elective office. We envisage foreign and domestic producer interests as expressing political support for a candidate via campaign contributions, and candidates as making trade policy pronouncements to maximize political support from producer interests. Tariffs are divisive, but VERs are consistent with conciliatory policy positions yielding mutual gain to foreign and domestic interests. No candidate has an interest in formulating a trade policy position using a tariff if a VER is a policy option. Protection in the developed countries has in recent years often taken the form of bilaterally negotiated voluntary export restraints (VERs) rather than the more traditional unilaterally imposed import restrictions.' The use of voluntary export restraints has been paralleled by interest in the theoretical literature. The effects of VERs have been compared with tariffs and quotas, and VERs have been examined in a political-economy framework with a view to identifying the gainers and losers from this form of restric